IMPLEMENTATION OF THE INCLUSION OF SELF-PROTECTION CLAUSES IN THE MAKING OF NOTARY DEEDS (STUDY AT THE NOTARY OFFICE DIMITRI DANANG SAWITRAWAN, S.H., M.KN.): IMPLEMENTASI PENCANTUMAN KLAUSULA PROTEKSI DIRI DALAM PEMBUATAN AKTA NOTARIS (STUDI DI KANTOR NOTARIS DIMITRI DANANG SAWITRAWAN, S.H., M.KN.) - Zulfa Verahardianti Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Notaries play a crucial role in drafting deeds, as they are legally authorized under the UUJN to perform this function. However, in practice, even when fulfilling their duties, obligations, and authority properly, notaries are often drawn into disputes between the parties involved. To prevent such risks, notaries frequently include a self-protection clause in the deeds they draft. This research addresses two main issues: (1) how the inclusion of self-protection clauses is implemented in notarial deeds, and (2) what form of legal protection is provided to notaries when clients disregard these clauses. The study employs an empirical legal research method with a sociological approach, using interviews and observations conducted at the office of Dimitri Danang Sawitrawan, S.H., M.Kn., a notary in Malang City. Data were analyzed deductively, moving from general legal provisions to specific cases. The findings reveal that a notary is not considered a party to the deed. Therefore, if disputes arise, the notary should not be implicated, either in criminal liability or as a defendant in civil cases. Legal protection remains valid even if the self-protection clause is absent, as long as formal requirements are met. As a precaution, notaries request supporting documentation such as photos, videos, or thumbprints to confirm parties’ approval of the deed.